The Acceptance of textbooks Writing Poetry-Based Love of The Country - Agung Nasrulloh Saputro (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This research is a development research that is difficult to develop textbook writing poetry based on love homeland. This development research refers to the Borg Gall stage model. The stage consists of ten stages of development, namely the stage of research and collection of preliminary information, the planning stage, the development stage of the initial production stage initial test phase, product revision phase, field trial phase, product revision stage, field test phase, , and dissemination and implementation. In this study only until the final product revision stage without including the phase of dissemination and implementation due to limited time research. In general, this study aims to explain the process of developing textbooks writing poetry based on love of the homeland. The results of the textbook development process are shown in the following stages. Validas textbooks were assessed by two validators, validation results indicated that the textbooks were included in either category because of the 75% percentage, the initial trial results were limited to seven class X students generated by student questionnaires, teacher interviews, and observer observations. From the results of field trials, students' grades in writing poetry resulted in an average score of 80 students.